An Investigation Of Modal Analysis For Al6061 Between Piezoelectric Film Sensor And Accelerometer - Ramli, Mohd Irman; Nuawi, Mohd. Zaki; Abdullah, Shahrum; Mohammad Rasani, Mohammad Rasidi; Thamburaja, P.; Ahmad, Muhamad Arif Fadli; Koh, Ko Seng (JBETE, 2017)
An experiment was conducted to determine modal parameters such as natural frequencies and mode shapes of aluminum 6061 (Al6061). A free dynamic vibration analysis was conducted to obtain the parameters. Al6061 was chosen as the experiment component mainly because of its wide application in automotive industries. Theoretically, if the component vibrates and produce frequency coherence with the natural frequency, resonance frequency will occur which can lead to structural failure. Modal analysis study was conducted by using both simulation and experimental method to compare their outcome. Simulation was conducted via ANSYS software while impact hammer testing was done for experimental work to determine the vibration parameter. Piezoelectric film and accelerometer were used as the sensor. The result obtained from simulation showed that frequencies for mode shape 1, 2 and 3 for circle shape were 134.60Hz, 324.73Hz and 727.52Hz. The result obtained from accelerometer showed that frequencies for mode shape 1, 2 and 3 for circle shape were 158.67Hz, 421.33Hz and 625.00Hz. Finally, the result captured from piezoelectric film sensor appeared that frequencies for mode shape 1, 2 and 3 for circle shape were 141.00Hz, 321.00Hz and 504.33Hz. There was a good results agreement between simulation and experimental work outcome.